2020
DOI: 10.1063/5.0031291
|View full text |Cite
|
Sign up to set email alerts
|

The relation between flame surface area and turbulent burning velocity in statistically planar turbulent stratified flames

Abstract: The relation between turbulent burning velocity and flame surface area for turbulent stratified flames has been analysed using a direct numerical simulation database. The simulations have been carried out for different initial turbulence intensities and initial integral length scales of equivalence ratio fluctuation for a given root-mean-square value in a globally stoichiometric mixture. Additionally, statistically similar turbulent premixed flames have been considered for comparison. The turbulent burning vel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 57 publications
4
18
0
Order By: Relevance
“…Note that the parameter defining the unburned gas cut-off point c (where c < šœ– c ) was tested with c = 0.0001 , 0.001 and 0.01 and it was found that there was no notable influence on the values of S T āˆ•S L and A T āˆ•A L . Recently, Brearley et al (2020) investigated a similar stratified flame DNS database to that considered here, without any scalar or turbulence forcing mechanisms, and found that S T āˆ•S L and A T āˆ•A L remained comparable to each other, and the results presented in Fig. 16 under scalar forcing are consistent with the previous findings by Brearley et al (2020).…”
Section: Modified Bandwidthsupporting
confidence: 86%
See 2 more Smart Citations
“…Note that the parameter defining the unburned gas cut-off point c (where c < šœ– c ) was tested with c = 0.0001 , 0.001 and 0.01 and it was found that there was no notable influence on the values of S T āˆ•S L and A T āˆ•A L . Recently, Brearley et al (2020) investigated a similar stratified flame DNS database to that considered here, without any scalar or turbulence forcing mechanisms, and found that S T āˆ•S L and A T āˆ•A L remained comparable to each other, and the results presented in Fig. 16 under scalar forcing are consistent with the previous findings by Brearley et al (2020).…”
Section: Modified Bandwidthsupporting
confidence: 86%
“…Recently, Brearley et al (2020) investigated a similar stratified flame DNS database to that considered here, without any scalar or turbulence forcing mechanisms, and found that S T āˆ•S L and A T āˆ•A L remained comparable to each other, and the results presented in Fig. 16 under scalar forcing are consistent with the previous findings by Brearley et al (2020).…”
Section: Modified Bandwidthsupporting
confidence: 86%
See 1 more Smart Citation
“…It has been shown elsewhere Chakraborty, 2010a, b, 2011a) that the laminar burning velocity variation with equivalence ratio is accurately captured using this thermo-chemistry. This simplification of chemical representation allows for a detailed parametric analysis in terms of u ļæ½ āˆ•S b( =1) and āˆ• (which was reported in detail by Brearley et al (2020)) with a reasonable amount of computational cost. The relative costs between simple and detailed chemistry DNS were discussed in detail by Keil et al (2021a).…”
Section: Numerical Implementationmentioning
confidence: 99%
“…To meet the objectives, a three-dimensional Direct Numerical Simulation (DNS) database of six statistically planar turbulent stratified flames has been considered (Brearley et al, 2020). This database consists of cases with a globally stochiometric mixture and an initially bimodal distribution of equivalence ratio in the unburned gas.…”
Section: Introductionmentioning
confidence: 99%